Association of alcohol dehydrogenase genes with alcohol-related phenotypes in a Native American community sample - Gizer, Ian R. (2011)
BACKGROUND: Previous linkage studies, including a study of the Native American population described in the present report, have provided evidence for linkage of alcohol dependence and related traits to chromosome 4q near a cluster of alcohol dehydrogenase (ADH) genes, which encode enzymes of alcohol metabolism. METHODS: The present study tested for associations between alcohol dependence and related traits and 22 single nucleotide polymorphisms (SNPs) spanning the seven ADH genes. Participants included 586 adult men and women recruited from eight contiguous Native American reservations. A structured interview was used to assess DSM-III-R alcohol dependence criteria as well as a set of severe alcohol misuse symptoms and alcohol withdrawal symptoms. RESULTS: No evidence for association with the alcohol dependence diagnosis was observed, but a SNP in exon 9 of ADH1B (rs2066702; ADH1B*3) and a SNP at the 5' end of ADH4 (rs3762894) showed significant evidence of association with the presence of withdrawal symptoms (p=0.0018 and 0.0012, respectively). Further, a haplotype analysis of these two SNPs suggested haplotypes containing either of the minor alleles were protective against alcohol withdrawal relative to the ancestral haplotype (p=0.000006). CONCLUSIONS: These results suggest that variants in the ADH1B and ADH4 genes may be protective against the development of some symptoms associated with alcohol dependence.